ANALISIS PENGGUNAAN MODEL I-O SEBAGAI PERANGKAT STATISTIK UNTUK PERENCANAAN KEGIATAN NON PERTANIAN DALAM EKONOMI MAKRO REGIONAL KOTA BANDAR LAMPUNG - Soelaiman, Achdiansyah (Indonesian Journal of Socio Economics)
The obyective of the study is to determine the economic structure of Bandar Lampung city and to figure out the contribution of economic sector as well as their linkages in regional economic development. The study employes I-O model to quantify overall economic structures in the region, including transaction of goods and services inter sectors, supply of goods and services inter economic sectors, demand of goods and services of all sectors, investment, consumption, and export-import. The study suggests that economic structure of Bandar Lampung city includes trades, hotel and restaurant service and services. All have contribution on the formation of Regional Gross Domestic Product of Bandar Lampung city. Sectors that have forward linkages are food industry, restaurant, hotels, and other services sectors.